2020
DOI: 10.1186/s13049-020-00765-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive accuracy of biomarkers for survival among cardiac arrest patients with hypothermia: a prospective observational cohort study in Japan

Abstract: Background There is limited information on the predictive accuracy of commonly used predictors, such as lactate, pH or serum potassium for the survival among out-of-hospital cardiac arrest (OHCA) patients with hypothermia. This study aimed to identify the predictive accuracy of these biomarkers for survival among OHCA patients with hypothermia. Methods In this retrospective analysis, we analyzed the data from a multicenter, prospective nationwide registry among OHCA pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the process of considering treatment strategy, if physicians can provide the critical prognostic information to the patients or their family members, they will make the better clinical decisions considering their values, preference and goals of care [ 6 ]. Although some predictors or prediction models in patients with accidental hypothermia have been developed, the reproducibility or generalizability of their predictive performance has not been adequately evaluated [ 7 13 ]. Therefore, a valid and reliable prediction model that has been evaluated by an external validation study is needed for decision-making based on evidence-based predictions of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of considering treatment strategy, if physicians can provide the critical prognostic information to the patients or their family members, they will make the better clinical decisions considering their values, preference and goals of care [ 6 ]. Although some predictors or prediction models in patients with accidental hypothermia have been developed, the reproducibility or generalizability of their predictive performance has not been adequately evaluated [ 7 13 ]. Therefore, a valid and reliable prediction model that has been evaluated by an external validation study is needed for decision-making based on evidence-based predictions of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the studies reporting the next most important outcomes of survival to discharge (4 observational studies; very low quality of evidence, downgraded for serious risk of bias and very serious indirectness) 110,114–116 and ROSC (5 observational studies; very low evidence, downgraded for serious risk of bias and very serious indirectness) 98,107,111,116,117 are similar to those reported for favorable neurologic outcome. In 1 report of 8 cats and 16 dogs in which blood samples were collected during ongoing CPR, blood potassium and sodium concentrations in animals with and without ROSC were not different 98 .…”
Section: Measurement Of Electrolytes and Other Blood Chemistry Compon...mentioning
confidence: 77%
“…The search strategy identified a total of 11,834 records, of which 6914 were non‐duplicates. After applying all inclusion and exclusion criteria, 118 studies were included in the scoping review, as shown in Figure 1 11–128 …”
Section: Resultsmentioning
confidence: 99%